PENGENALAN FO’OGUNA’O DALU-DALU FOKHO MBU’U DI GUNUNGSITOLI-NIAS MELALUI APOTIK IMAN - Tatema Telaumbanua Tatema Telaumbanua (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The more developed the progress of an area then, the illness suffered also develops. No exception to the disease suffered by the people in the village of Fadoro, fooguna; o in the past, fokho mbu'u is very helpful if they know firsthand what is the effective medicine for the community. Most of these diseases are felt and experienced by parents who are aged around 40-60 years. So the handling of this disease is to reduce and eliminate inflammation that occurs. Even so, rheumatoid arthritis itself cannot be completely cured. Drugs that can be given to people with rheumatoid arthritis include: non-steroidal anti-inflammatory drugs, steroids, vitamins and other supplements. So by giving introduction knowledge to the people in the fadoro village of Gunungsitoli City.